INTEGRATION OF TECHNOLOGY-BASED INTERNAL CONTROL SYSTEMS TO MINIMIZE THE RISK OF BAD DEBTS IN MICRO CREDIT PROGRAMS - Permata, Rr Fatmasari Muliawati; Juanda, Ahmad; Leniwati, Driana (Jurnal Aplikasi Akuntansi, 2025)
This study aims to conduct an in-depth analysis of integrating technology-based internal control systems to minimise the risk of bad debts in micro credit programs. This study is a qualitative case study at Bank X, as it is one of the state-owned banks with the highest disbursement of micro credit loans in Indonesia. Data collection techniques included in-depth interviews, participatory observation, documentation, and literature review, which were analysed through the reduction stages, data display, and conclusion. The research results indicate that using technology in Bank X's monitoring and evaluation system has significantly impacted the effectiveness of managing the bad debt risk. Technology enables real-time monitoring processes, accelerates claim submissions and verifications, and enhances the accuracy of the data required for decision-making processes. Challenges in technology implementation include inter-institutional system integration and customer digital literacy issues. Continued efforts to strengthen the internal control system through digitalisation maintain the quality of credit disbursement and demonstrate readiness to address the risks inherent in national-scale productive financing programs. Further research could be conducted at multiple research sites to identify differences between entities that have implemented technology and those that have not. This study contributes to filling a gap in research that examines the practical integration of technology in bank internal control to lower the risk of bad debts.